Mechanics and Failure of Structured Interfaces - Heide-Jørgensen, Simon (AU Library Scholarly Publishing Services, 2019)
This dissertation concerns heterogeneous, structured interfaces’ mechanics and failure, in particular the load response, critical fracture energy and crack kinetics. During the project eight manuscripts have been prepared and submitted to scientific journals. Five of these are included here forming the main body of the dissertation. The topics of these include development and test of a new nano-adhesive based on polymer brushes to bond rubber and metal, a novel peel test specimen comprising a heterogeneous geometry, consequences of zones of weak adhesion, bridging of a support carrier in the bondline, and, macro- and micromechanical behavior of pillar-structured interfaces. Analytical modeling and numerical simulations backed up by experimental testing were used to study these, among others.